Creating Anamorphic Illusions with Microsoft Kinect - Spiegel, David; Fellom, Nathan; Kryzer, Nicholas (My University, 2015)
A perspective anamorphosis distorts an image such that it requires the viewer to look from a specific vantage point for the image to appear undistorted. Often seen in sidewalk art, this projection can create an illusion of depth on a flat surface. Our goal was to use data from a Microsoft Kinect to change the vantage point of our anamorphic image to match the position of the viewer. With this technique we can produce the illusion of 3 dimensions without requiring 3D glasses.
Color poster with text, images, and models.
Keywords: Microsoft Kinect; 3-D illusions; Anamorphic illusions; Posters